If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 3) + 2x = 37 Reorder the terms: 2(3 + 2x) + 2x = 37 (3 * 2 + 2x * 2) + 2x = 37 (6 + 4x) + 2x = 37 Combine like terms: 4x + 2x = 6x 6 + 6x = 37 Solving 6 + 6x = 37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 37 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 37 + -6 6x = 37 + -6 Combine like terms: 37 + -6 = 31 6x = 31 Divide each side by '6'. x = 5.166666667 Simplifying x = 5.166666667
| 7+5n=3n+5 | | x+x+3=5-2(x-5) | | 5/6y=7-11/12y | | x-6-(10x-8)= | | 3+8q=6+7q | | -3a-8(-5a-1)= | | 4p^2+164p+81=0 | | (3x-9)=(2x+31) | | B-4+6b=23 | | 1/6-3x/2=x/4-1/4 | | 3x-4(x+2)=3(4-2x)+8 | | 3/2=21/x | | 3x-1/2x | | b+.66666=2 | | f(1/2)=1/2+9.5 | | -17+20= | | -6(v-4)=18-5v | | x/6-x/12+8=x+8 | | 5y-8-3y+3=0 | | 3/4w=75 | | V-24=-7 | | 12y^2-22y+6=0 | | 8x-2=20x+7 | | 3z-2+5=9 | | x^2=(6/11x)+(135/121) | | -9-(-11)= | | (2x+3)(x)=37 | | 2x+8/4=7x-10/9 | | x(7+x)=6(4+6) | | 2-1/x-5/x^2=0 | | 28+3=x | | -2a4/-3b-7 |